STUDI DESKRIPTIF ZONA TOLERANSI OPERATOR SELULER DI SURABAYA - Cindy Priscillia; Erna Andajani; Werner Ria Murhadi (CALYPTRA, 2018)
This study aims to describe the zone of tolerance of the three largest mobile operators Telkomsel, Indosat, and XL in Surabaya. This zone of tolerance is obtained by measuring the gap of customer expectations (desired service and adequate service) on the quality of service provided. The results of this study show that the three mobile operators have been able to meet minimum servicequality that customers want (adequate service) but does not meet the actualservice quality desired by the customers (desired service) Telkomsel has the most excellent service quality between the three providers and then followed by XL and Indosat. The wider zone of tolerance is owned by Indosat, followed by XL and then Telkomsel.